Pembinaan Karakter Siswa Berbasis Ecolistic melalui Program Pondok Ramadhan: Integrasi Pengabdian kepada Masyarakat dan PPL di SMAN 20 Surabaya - Eli Masnawati; Chatarini Septi Ngudi Lestari (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
This community service study aims to analyze the implementation of an ecolistic-based student character development model through the Pondok Ramadhan program, integrating community service (PKM) and teaching practicum (PPL) at SMAN 20 Surabaya. The program was conducted from 23 to 26 February 2026, involving approximately 900 students and a collaborative partnership among lecturers, postgraduate students of Islamic Education, and school stakeholders. The study employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings indicate that the integration of PKM and PPL creates a collaborative, holistic, and participatory learning ecosystem. The ecolistic approach, which integrates spiritual (ilahiyah), social (insaniyah), and contextual (kauniyah) dimensions, proves effective in enhancing students’ religious character, social ethics, and moral awareness, particularly in responding to the challenges of the digital era. Furthermore, the program contributes to improving postgraduate students’ pedagogical, professional, and spiritual competencies through authentic learning experiences. The novelty of this study lies in the development of an integrative PKM–PPL model based on an ecolistic approach as an adaptive strategy for character education tailored to Generation Z. This program demonstrates that experiential religious activities can serve as an innovative and sustainable model for contextual character education.